45. CLINICAL APPLICATIONS OF STEM CELL THERAPY IN OTORHINOLARYNGOLOGY (Vietnam Journal of Community Medicine, 2024)
Aims of review: Overview of applications stem cell technology and regenerative medicine in the treatment of ear, nose and throat (ENTs) diseases.Methods and Literature Overview: The research design is a general study. We conducted a search using databases such as PubMed and Google Scholar. Our selection criteria included clinical studies related to stem cell-based treatments ear reconstruction, hearing loss, olfactory dysfunction and larynx disorders. The number of articles meeting the review criteria includes 107 articles.Results: Clinical studies show that the immune response is reduced, demonstrating that the biocompatibility of graft materials is improved and the treatment effectiveness is equivalent to previous methods. Safety and effectiveness of stem cells in the treatment of ENTs diseases.Conclusion: Although recent reports are primarily from clinical trials at phases I and II or patient cases, the results have shown the superiority, safety and effectiveness of stem cell therapy in the treatment of ear, nose and throat diseases.
Keywords: Stem cells, Otorhinolaryngology, regenerative medicine, head and neck surgery